Peran Sains dalam Membangun Kualitas Generasi Islam (Role of Science in Building Quality of Islamic Generations) - Muhamad Iqbal Ramadhan; Yazid Habibullah; Alfina Wildatul Fitriyah (STIKes Ibnu Sina Ajibarang, 2024)
Science is always associated with general science or science that studies worldly matters only. Some Muslims think that science has nothing to do with Islam or in other words Islam does not need science. If the assumption of the Islamic community about this still exists then Islam is in the danger zone, because actually Islam needs science. Islam and science are not two opposing camps, but two very solid camps. If we look deeper, the Qur'an presents many verses about science. The verses of the Qur'an about science range from 750 to 1000 verses. In fact, the first revelation that came down to the Prophet Muhammad SAW, namely the command to read. In the Qur'an it has been explained that paying attention to the universe which means also studying science is part of reading the verses of Allah SWT. Meanwhile, the results of research conducted by scientists about the universe do not contradict the Qur'an which was revealed 1400 years ago. If science and technology are only controlled by non-Muslims, then Muslims will be considered weaker and lower in the field of science. Therefore, Islam needs the next generation of people who love and understand the contents of the Qur'an and are not blind to science, especially science. Islam will flap its wings more in the field of science and technology so that a generation of IMTAQ and IPTEK is formed, namely a generation of Muslims who have faith and piety and master science and technology. Science is also important in the development of Islam because science brings knowledge that is very important in future generations and science also plays an important role for all people in this world. In the context of building the quality of the Islamic generation, there are several important aspects that need to be considered, namely;